PERAN PENGENDALIAN KUALITAS DAN KEPEMIMPINAN PRODUKSI DALAM PENINGKATAN EFESIENSI DALAM PRODUKTIVITAS PADA BAGIAN HANDSTITCHING DI PABRIK PLUSH TOYS PT WAI HING INDUSTRIAL - Setyowati, Mega; Hamdani, Hamdani (Commodity : Jurnal Perbankan dan Keuangan Islam, 2025)
This study aims to analyze the role of quality control and production leadership in improving the efficiency and productivity of operators in the handstitching section at the Plush Toys Factory at PT Wai Hing Industrial. As a handstitching leader, the author is directly involved in sewing quality control, daily target adjustments, production reporting, and operator absence control. This study uses a qualitative descriptive method with a case study approach. The results show that the effectiveness of quality control has a direct impact on the level of product defects and the achievement of daily targets. Communicative leadership and disciplined supervision contribute to increased operator productivity.